2014
DOI: 10.4103/0255-0857.124300
|View full text |Cite
|
Sign up to set email alerts
|

Species distribution and drug susceptibility of candida in clinical isolates from a tertiary care centre at Indore

Abstract: Species-level identification of Candidaand their antifungal sensitivity testing should be performed to achieve better clinical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 18 publications
7
30
2
Order By: Relevance
“…Result of our study has shown that a maximum number of the isolates were from male patients and elder population were mostly effected which is with the agreement of the study done by Pahwa et al [4] We are not the first to report that diabetics were one of the most common predisposing factors for candidiasis other investigator also reported the same [11]. These findings indicate that due to the poor immune response by elderly patients and predisposing factor such as diabetes mellitus may act as an important risk factor for candidiasis.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Result of our study has shown that a maximum number of the isolates were from male patients and elder population were mostly effected which is with the agreement of the study done by Pahwa et al [4] We are not the first to report that diabetics were one of the most common predisposing factors for candidiasis other investigator also reported the same [11]. These findings indicate that due to the poor immune response by elderly patients and predisposing factor such as diabetes mellitus may act as an important risk factor for candidiasis.…”
Section: Discussionsupporting
confidence: 92%
“…Several other investigator form India also reported a high prevalence of Candida causing UTI [4]. However, the incidence of invasive isolates was less in our study isolates in compare to other studies where they had found a high prevalence of invasive isolates in their study population [9,10].…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…The samples were taken from the oral cavity of the elderly, and this percentage shows a high resistance. In a study in patients admitted to the intensive care unit, non -albicans strains showed a high resistance to azoles (15).…”
Section: Discussionmentioning
confidence: 99%